IPS GO WEBSITE LEARNING MEDIA: IMPROVING STUDENTS' CRITICAL THINKING SKILLS - Syafidah, Qurota Yunus; Ananta, Okki Lavio; Alrianingrum, Septian; Mardin, Marlita (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Critical thinking is essential in dealing with today's information complexity because it allows individuals to make informed decisions and overcome challenges in a systematic way. Several media have been developed to support the development of these skills so an evaluation of the media's effectiveness is needed. The purpose of this study is to determine if students' critical thinking abilities may be enhanced by using the IPS GO internet learning media. An experimental approach with a pretest-posttest design for a single group is used in this study. Forty students from a Madiun City school were the subjects of this study. Tests and observations are used to gather data for this study. The t-test and N-Gain are two quantitative tools used in research data analysis. According to the study's findings, students' critical thinking abilities are significantly impacted by using the IPS Go website's learning media. An N-Gain rating of 0.37, or 37%, indicates an improvement in conceptual comprehension or mastery. Thus, junior high school students critical thinking abilities can be enhanced by using the learning media on the IPS GO website